“Evaluating the impact of climate change on drought risk in semi-arid region using GIS technique” - Rinali Patel; Anant Patel (Results in Engineering, 2024)
This GIS study examines how climate change affects drought risk in semi-arid regions. Semi-arid regions are especially vulnerable to droughts due to rising global temperatures and changing precipitation patterns. The study analyses drought trends using diverse dataset, including climate projections, geographical information, and environmental parameters. The study incorporated temperature, precipitation, and moisture data, alongside land cover, soil type, and land usage information. Sabarmati River Basin residents and ecosystems need drought management and adaptation. We studied climate change using temperature, precipitation, and moisture data. Plant cover, soil type, and land usage indicated regional drought. GIS, meteorological, and environmental data projected drought. Drought risk model includes LULC, VCI, LST, SMI, and NDDI by integrating all parameters such as LULC, NDVI, Rainfall, etc. all meteorological and environmental data using GIS. Climate and land use changes increased drought risk in the study region. GIS-based drought indices and risk assessment models quantify and map drought intensity, frequency, and duration under different climate change scenarios. The results help semi-arid regions develop adaptive drought risk management strategies. This interdisciplinary approach emphasises the ability of GIS for assessing and mitigating climate-induced drought occurrences.